Angelic Encounters as Reported by Burn Survivors. (September 2021) - Royse, David
After collecting personal accounts of near-death experiences from persons with large burn injuries, it was discovered that several of the participants described seeing, talking with (and even hugging and praying with) a person or spirit they identified as an angel. Although the number of individuals in this qualitative study is small ( n = 6), verification of some key details in these interesting accounts may have been possible if one had the inclination and resources to investigate at the time. The author suggests helping professionals may want to consider that some patients may be able to relate other anecdotal accounts and a collection of these could assist with understanding their prevalence and could be a source of comfort to those experiencing great pain, loss, or crisis in their lives.